On physical‐layer security for primary system in underlay cognitive radio networks. Issue 2 (1st March 2018) - Xie, Ping; Zhang, Moli; Zhang, Gaoyuan; Zheng, Ruijuan; Xing, Ling; Wu, Qingtao
Abstract : In this study, the authors consider the physical‐layer security for transmission in underlay cognitive radio networks, where consisting of a primary source–destination pair, a secondary transmitter–receiver pair and a common eavesdropper (E). To transmit data in a secure and reliable manner, they propose a transmission protocol for an underlay cognitive radio network. In particular, the secondary user is allowed to operate on the primary spectrum bandwidth when the interference threshold is satisfied. To protect the transmission confidentiality of primary system, PS node transmits a signal, which is linearly combined with the jamming signal (as artificial noise) and expectation signal, to interfere E. Furthermore, they propose a superimposed coding to combine with the artificial noise and expectation signal at PS node. We also analyse the performance of the proposed transmission protocol. We obtain the outage probability of secondary and primary systems. Simultaneously, they derive the closed‐form expression of intercept probability for primary system. In addition, they verify the performance of their proposed transmission protocol by numerical experiment. The numerical results show that their proposed transmission protocol not only has the better outage performance for secondary system but also has the better intercept performance for primary system.